2000
DOI: 10.1007/s100380050209
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of the human DA41 gene and its mapping to chromosome 9q21.2–q21.3

Abstract: DA41 was previously identified as one of the DAN-binding proteins, via a yeast-based two-hybrid screening strategy. In the present study, we cloned a human homolog of DA41 cDNA. Structural analysis revealed that human DA41 cDNA consisted of 2,861 nucleotides in length and encoded a protein of 589 amino acids, with a predicted molecular mass of 62.4 kDa. Human DA41 exhibited an 86% amino acid sequence identity to rat DA41, indicating the evolutionarily conserved structure and function of DA41. A database search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Finally, it can be also appreciated in that figure that many among the samples with the highest total levels of expression, obtained adding together all ubiquilin genes, come from the nervous system (see e. g. hypothalamus, cerebral cortex, cerebellum, etc.) in good agreement with previous data [6,11]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, it can be also appreciated in that figure that many among the samples with the highest total levels of expression, obtained adding together all ubiquilin genes, come from the nervous system (see e. g. hypothalamus, cerebral cortex, cerebellum, etc.) in good agreement with previous data [6,11]. …”
Section: Resultssupporting
confidence: 93%
“…On one hand, UBQLN1 is broadly expressed, but no particularly low expression in testis in detected (this is clearly seen in Figure 7). This is probably a real result, given that a relatively high level of expression in testis was observed before [11]. On the other hand, expression in whole brain samples for UBQLN4 appears as one of the lowest.…”
Section: Resultsmentioning
confidence: 55%
“…24) In their experimental systems, the overall levels of CDK2 and p27 kip1 did not change upon treatment with VP16, though there was a significant , that can bind to cyclin A and inhibit the degradation of cyclin A. 9) XDRP1 showed marked sequence homology with DA41 7) and overexpression of XDRP1 in frog embryos blocked embryonic cell division.…”
Section: Discussionmentioning
confidence: 92%
“…6) Additionally, we have reported that human DA41 was mapped to chromosome 9q21.2-q21.3, a position overlapping the candidate tumor suppressor locus for bladder cancer. 7) A recent search of the databases for DA41-related protein(s) identified mouse PLIC-1, PLIC-2, frog XDRP1 and yeast DSK2. [7][8][9][10] PLIC-1 and PLIC-2 interact with the cytoplasmic tail of integrin-associated protein (IAP) and mediate the interaction between IAP and vimentin-containing intermediate filaments.…”
mentioning
confidence: 99%
See 1 more Smart Citation